Fuglede – Putnam type theorems for extension of M-hyponormal operators - Mecheri , S.; Prasad , T. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.9 We consider k-quasi-M-hyponormal operator T B(H) such that TX = XS for some X B(K,H) and prove the Fuglede–Putnam type theorem when adjoint of S B(K) is k-quasi-M-hyponormal or dominant operators. We also show that two quasisimilar k-quasi-M-hyponormal operators have equal essential spectra.